PROVING TRIGONOMETRIC IDENTITIES

Proving Trigonometric Identities :

Here we are going to see, some example problems to show proving trigonometric identities.

Proving Trigonometric Identities - Questions

Question 1 :

Prove the following identities.

(i) cot θ + tan θ = sec θ cosec θ

Solution :

L.H.S :

cot θ  =  cos θ / sin θ

tan θ  =  sin θ / cos θ

The reciprocal formula for 1/sin θ is coesec θ and 1/cos θ is sec θ.

Hence it is proved.

(ii) tan4 θ + tan2 θ = sec4 θ − sec2 θ

Solution :

L.H.S :

tan4 θ + tan2 θ  =  (tan2 θ)2tan2 θ

  =  tan2 θ(tan2 θ + 1)

  =  tan2 θ(sec2 θ)

  =  (sec2 θ - 1)(sec2 θ)

  =  sec4 θ - sec2 θ

R.H.S

Hence it is proved.

(2)  Prove the following identities.

(i)  (1 - tan2 θ) / (cot2 θ - 1)  =  tan2 θ

Solution :

L.H.S

  =  (1 - tan2 θ) / (cot2 θ - 1)

Formula for tan θ and cot θ 

cot θ  =  cos θ / sin θ

tan θ  =  sin θ / cos θ

  =  tan2 θ

  R.H.S

Hence it is proved.

(ii) cos θ/(1 + sin θ)  =  sec θ + tan θ

Solution :

L.H.S

  =  cos θ/(1 + sin θ) 

By multiplying the conjugate of denominator, we get

  =  [cos θ/(1 + sin θ)] [(1 - sin θ)/(1 - sin θ)]

  =  [cos θ(1 - sin θ)/(1 - sin θ)(1 + sin θ)]

  =  [cos θ(1 - sin θ)/(1 - sinθ)]

  =  [cos θ(1 - sin θ)/cosθ]

  =  (1 - sin θ)/cos θ

  =  (1/cos θ) - (sin θ/cos θ)

  =  sec θ - tan θ

(3)  Prove the following identities.

(i)  √[(1 + sin θ)/(1 - sin θ)]  =  sec θ + tan θ

Solution :

L.H.S

  =  (1/cos θ) + (sin θ/cos θ)

  =  sec θ + tan θ

  =  R.H.S

Hence proved.

(ii)  [√(1 + sin θ)/(1 - sin θ)] + [√(1 - sin θ)/(1 + sin θ)]  = 2 sec θ

Solution :

L.H.S 

   =   [√(1 + sin θ)/(1 - sin θ)] + [√(1 - sin θ)/(1 + sin θ)]

  =  2/cos θ

  =  2 sec θ

R.H.S 

Hence proved .

(4)  Prove the following identities.

(i) secθ = tan6 θ + 3 tan2 θ sec2 θ + 1

Solution :

R.H.S 

 tan6 θ + 3 tan2 θ sec2 θ + 1

  =  (tan2 θ)3 + 3 (tan2 θ) (sec2 θ) + 1

(a + b)3  =  a3 + b3 + 3ab (a + b) 

  =  (tan2 θ)3 + 3 (tan2 θ) 1 (tan2 θ + 1) + 13

=  (tan2 θ + 1)3

=  (sec2 θ)3

=  sec6 θ

R.H.S

Hence proved.

(ii) (sin θ + sec θ)2 + (cos θ + cosec θ)2 = 1 + (sec θ + cosec θ)2

Solution :

L.H.S :

  =  (sin θ + sec θ)2 + (cos θ + cosec θ)2

  =  sin2 θ + sec2 θ + 2 sin θ sec θ + cos2 θ + cosec2 θ + 2 cos θ cosec θ

  =  (sin2 θ + cos2 θ) + sec2 θ  + cosec2 θ + 2 (sin θ sec θ + cos θ cosec θ)

  =  1 + sec2 θ  + cosec2 θ + 2 [(sin θ/cos θ) + (cos θ/sin θ)]

  =  1 + sec2 θ  + cosec2 θ + 2 [(sin2θ + cos2θ)/cos θ sin θ)]

  =  1 + sec2 θ  + cosec2 θ + 2 (1/cos θ sin θ)

  =  1 + sec2 θ  + cosec2 θ + 2 secθ cosec θ 

  =  1 + (sec θ  + cosec θ)2

R.H.S

Hence proved.

After having gone through the stuff given above, we hope that the students would have understood, "Proving Trigonometric Identities". 

Apart from the stuff given in this section "Proving Trigonometric Identities"if you need any other stuff in math, please use our google custom search here.

Widget is loading comments...